Human fertilization: epididymal hCRISP1 mediates sperm zona pellucida binding through its interaction with ZP3 - Maldera, Julieta Antonella (2014)
Human epididymal CRISP1 (hCRISP1) associates with sperm during maturation and participates in gamete fusion through egg complementary sites. Its homology with both rodent epididymal CRISP1 and CRISP4 reported to participate in the previous stage of sperm binding to the zona pellucida (ZP), led us to further investigate the functional role of hCRISP1 by studying its involvement in human sperm-ZP interaction. Human hemizona (HZ) were inseminated with human capacitated sperm in the presence of either anti-hCRISP1 polyclonal antibody to inhibit sperm hCRISP1, or bacterially-expressed hCRISP1 (rec-hCRISP1) to block putative hCRISP1 binding sites in the ZP. Results revealed that both anti-hCRISP1 and rec-hCRISP1 produced a significant inhibition in the number of sperm bound per HZ compared with the corresponding controls. The finding that neither anti-hCRISP1 nor rec-hCRISP1 affected capacitation-associated events (i.e. sperm motility, protein tyrosine phosphorylation or acrosome reaction) supports a specific inhibition at the sperm?egg interaction level. Moreover, immunofluorescence experiments using human ZP-intact eggs revealed the presence of complementary sites for hCRISP1 in the ZP. To identify the ligand of hCRISP1 in the ZP, human recombinant proteins ZP2, ZP3 and ZP4 expressed in insect cells were co-incubated with hCRISP1 and protein?protein interaction was analyzed by ELISA. Results revealed that rec-hCRISP1 mainly interacted with ZP3 in a dose-dependent and saturable manner, supporting the specificity of this interaction. Altogether, these results indicate that hCRISP1 is a multifunctional protein involved notonly in sperm?egg fusion but also in the previous stage of sperm?ZP binding through its specific interaction with human ZP3.